Risk Factors for Progression in Vestibular Schwannomas After Incomplete Resection: A Single Center Retrospective Study - Li, Jiuhong; Deng, Xueyun; Ke, Daibo; Cheng, Jian; Zhang, Si; Hui, Xuhui (Frontiers in Neurology, 2021)
Background and Purpose: The risk factors for progression in vestibular schwannomas (VSs) after incomplete resection remain to be elucidated. The purpose of this study was to investigate the risk factors for progression in remnant VSs after surgery. Methods: From January 2009 to January 2018, 140 consecutive patients, underwent incomplete resection of VSs via suboccipital retrosigmoid approach in our institution were retrospectively analyzed. During follow-up, if progression was detected, the patient was classified into Progressive Group (PG); if the residual tumor were stable or shrank, the patient was classified into Stable Group (SG). Univariate analysis and multivariate analysis were used to evaluate the risk factors for progression after incomplete resection of VSs. Results: After a mean follow-up of 80.4mo (range, 24-134mo), 35 (25.0%) patients (Progressive Group) had a progression, and no progression was detected in 105 (75.0%) patients (Stable Group). The average tumor size was 36.5±8.9mm in PG and 31.0±9.8mm in SG respectively. The residual tumor volume was 304.6±443.3mm3 in PG, and 75.9±60.0mm3 in SG respectively. Univariate analysis showed preoperative tumor size, residual tumor volume, and irregular internal auditory canal (IAC) expansion were significantly different between two groups. While gender, age, cystic component, or Ki-67 labeling index did not differ significantly between the two groups. Multivariate analysis showed residual tumor volume was the independent risk factor for progression. Conclusions: VSs underwent incomplete resection with larger preoperative size, greater residual tumor volume, or irregular IAC expansion may have a higher progression rate. Strict follow-up with shorter interval in these patients to detect early progression is necessary.